. Pengaruh Konseling Kelompok dengan Teknik Deep Breathing terhadap Kecemasan Komunikasi Interpersonal Siswa Kelas VII SMP Negeri 1 Lebong - I Wayan Dharmayana; Ahnaf Fikrah; Rita Sinthia (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aimed to describe the effect of group counseling with deep breathing techniqueson students’ interpersonal communication anxiety. This study used an experimentalmethod with a one-group pretest-posttest design. The population in this study werestudents of class VII.2 SMP Negeri 1 Lebong, amounting to 32 students. The sample wasdetermined to be six students with a very heavy level of interpersonal communicationanxiety, using a purposive sampling technique. Data was collected using a questionnairewith the DASS (Depression Anxiety Stress Scale) measurement scale. Data were analyzedusing the t test (paired sample t-test). The results showed that there was a decrease instudents’ interpersonal communication anxiety levels after being given group counselingtreatment with deep breathing techniques. The results of hypothesis testing show the valueof t = 6,697 (p < 0.05). This means that there is a significant effect of treatment onstudents’ interpersonal communication anxiety with deep breathing techniques on studentsof SMP Negeri 1 Lebong.